A mechanical, leaching and radiological assessment of fired bricks with a high content of fly ash. Issue 11 (1st August 2018) - Leiva, C.; Rodriguez-Galán, M.; Arenas, C.; Alonso-Fariñas, B.; Peceño, B.
Abstract: All building materials contain amounts of natural radioactive nuclides and heavy metals, but when waste materials are to be used in building materials, industrial processing can lead to further enhancement of the concentrations of nuclides and heavy metals in the waste. In this paper fly ashes were used as a raw material to replace natural clay to make fired bricks. The effects of a high replacement ratio (from 0% to 100%) of clay with fly ash on the mechanical, radiological and leaching properties of bricks were analyzed. A study of the different sintering temperatures of bricks was carried out at the selected temperatures of 800, 900 and 1000 °C. When the temperature was increased the mechanical strength was also increased. Two leaching tests (one batch and the other monolithic) were carried out and the bricks with a high replacing ratio did not present problems regarding the heavy metal leaching in either test. The contents of three radionuclides ( 220 Ra, 232 Th and 40 K) were analyzed and the Activity Concentration Index of the bricks was calculated and was lower than 1, indicating a radiation exposure lower than 1 mSv y −1 .